2013
DOI: 10.1111/ijcp.12264
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter species infection may be associated with cholangiocarcinoma: a meta-analysis

Abstract: Our meta-analysis supports the possible association between Helicobacter species infection and cholangiocarcinoma. Further investigations are required to clarify the role of Helicobacter species in this malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…Some of them have been found in humans, including H. bilis , H. cinaedi , and H. fennelliae . Besides occasional associations with gastroenteritis,365 infection with these and other enterohepatic Helicobacter species have been associated with extraintestinal diseases, including extrahepatic cholangiocarcinoma for H. bilis and H. hepaticus 366 367 and bacteraemia 368. In addition to these enterohepatic Helicobacter species, gastric non- H. pylori Helicobacter species have also been detected in humans.…”
Section: Working Group 5: H Pylori and The Gastric Microbiotamentioning
confidence: 99%
“…Some of them have been found in humans, including H. bilis , H. cinaedi , and H. fennelliae . Besides occasional associations with gastroenteritis,365 infection with these and other enterohepatic Helicobacter species have been associated with extraintestinal diseases, including extrahepatic cholangiocarcinoma for H. bilis and H. hepaticus 366 367 and bacteraemia 368. In addition to these enterohepatic Helicobacter species, gastric non- H. pylori Helicobacter species have also been detected in humans.…”
Section: Working Group 5: H Pylori and The Gastric Microbiotamentioning
confidence: 99%
“…On this subject, Xiao et al. performed a meta‐analysis showing a positive association between Helicobacter species and cholangiocarcinoma.…”
Section: Hepatobiliary Diseasesmentioning
confidence: 99%
“…Concerning cholangiocarcinoma, a positive association with some defined conditions, including diabetes, IBD, and peptic ulcer caused by H. pylori, is a well-known risk factor [61]. On this subject, Xiao et al [62] performed a meta-analysis showing a positive association between Helicobacter species and cholangiocarcinoma.…”
Section: Hepatobiliary Diseasesmentioning
confidence: 99%
“…The importance of single risk factors, such as bacterial infection, can be hard to gauge. A meta-analysis revealed that Helicobacter species in the hepatobiliary system are associated with CCA globally, as well as in liver fluke-free areas (4). One member of the genus, Helicobacter pylori, has also been classified as a group I carcinogen and is common in the gastroduodenal system (3).…”
mentioning
confidence: 99%